Transformation of Spiral and Straight Schemes of Thinking in Translation (on Material of Chinese and Russian Languages) - L. An; Y. Gao (Научный диалог, 2018)
The problem of differences in the thought patterns of native speakers of Chinese and Russian languages is considered. The question is raised about the difficulties of translation related to structural differences of the two languages, determined by the spiral and straight patterns of thought. It is shown that when translating the texts from Chinese into Russian the transformation of the spiral scheme of thought of the Chinese language in the straight pattern of thought of the Russian language takes place. The article presents substantial structural differences in the grammatical structure of sentences in Chinese and Russian, having a significant impact on the translation and reception of the text. It is noted that the differences in language are determined by the Western and Eastern types of thinking. In particular, the opposition of human and nature in Western philosophy is emphasized, that results in the implementation of the straight schema of thinking syntax of the Russian language. In turn, ideas about the unity of man and nature in the Eastern philosophy predetermined the spiral scheme of thinking presented in the Chinese language. In conclusion the author states that different types of thinking create difficulties in translation, which require interpretation.